2007
DOI: 10.1093/eurheartj/ehm239
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the alpha-cardiac actin gene associated with apical hypertrophic cardiomyopathy, left ventricular non-compaction, and septal defects

Abstract: LVNC and HCM may appear as overlapping entities. The ACTC E101K mutation should be considered in the genetic diagnosis of LVNC, apical HCM, and septal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
127
1
24

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(153 citation statements)
references
References 34 publications
1
127
1
24
Order By: Relevance
“…More than 600 mutations have been discovered to be associated with HCM with all but a few in the genes coding for the contractile apparatus of the myofibril, predominantly myosin-binding protein C and ␤-myosin heavy chain (3)(4)(5)(6). Eleven mutations have been identified in the cardiac actin gene, ACTC (7)(8)(9)(10)(11), including the E99K mutation that has been intensively investigated as it has been shown to co-segregate with an unusual apical hypertrophic phenotype (12,13). HCM is defined clinically as the presence of unexplained ventricular hypertrophy; usually the thickening is most prominent in the interventricular septum, but other pathologies can also occur, such as apical and concentric hypertrophy or left ventricular noncompaction.…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%
See 2 more Smart Citations
“…More than 600 mutations have been discovered to be associated with HCM with all but a few in the genes coding for the contractile apparatus of the myofibril, predominantly myosin-binding protein C and ␤-myosin heavy chain (3)(4)(5)(6). Eleven mutations have been identified in the cardiac actin gene, ACTC (7)(8)(9)(10)(11), including the E99K mutation that has been intensively investigated as it has been shown to co-segregate with an unusual apical hypertrophic phenotype (12,13). HCM is defined clinically as the presence of unexplained ventricular hypertrophy; usually the thickening is most prominent in the interventricular septum, but other pathologies can also occur, such as apical and concentric hypertrophy or left ventricular noncompaction.…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%
“…The ACTC E99K mutation is the subject of an extensive ongoing clinical study with 76 mutation carriers in 10 families currently identified (13). This mutation is associated with a unique form of hypertrophy where the apex of the heart is thickened, with a phenotype overlapping both HCM and left ventricular hypertrabeculation/noncompaction.…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the p.(Ala21Val) mutation strongly cosegregates with the disease, providing additional support for its pathogenicity. ACTC1 gene mutations have been phenotypically related with diverse cardiac anomalies, including dilated cardiomyopathy,17 hypertrophic cardiomyopathy,18, 19, 20 myocardial noncompaction,8, 21 and congenital heart defects, in particular atrial septal defect 22…”
Section: Discussionmentioning
confidence: 99%
“…Other genes whose mutations have been implicated in both HCM and LVNC are TPM1 and MYBPC3 , encoding for tropomyosin 1 and cardiac myosin binding protein‐C, respectively 7, 8, 9, 10, 11, 12, 13…”
mentioning
confidence: 99%